Compared to the Justice Procedure Act and the Kuhap Provision Providing Free Legal Advice to Suspects - Muh Sutri Mansyah; Kaswandi Kaswandi; Sulayman Sulayman; Agus Agus; Rajasree Rajasree (Indonesian Journal of Law and Islamic Law (IJLIL), 2024)
The aim of the research is to examine the comparison of jinayat procedural law with kuhap in providing free legal advice to suspects, the method used is normative juridical with statutory and conceptual approaches, primary legal material: Aceh Qanun Number 7 of 2013 concerning Jinayat Procedural Law and Laws Number 8 of 1981 concerning Criminal Procedure Law, secondary legal materials: journal articles, books, etc. The analysis technique used is descriptive analysis and the interpretation used is grammatical and systematic interpretation. The results of the research show that in the procedural law of jinayat a person who is given the assistance of a legal advisor is threatened with 60 (sixty) lashes or 1200 (one thousand two hundred) grams of pure gold as a fine or 60 (sixty) months in prison or more or for those who cannot afford it. Meanwhile, the criminal procedure law limits the provision of legal advice to only suspects who face a prison sentence of five years or more and the death penalty or a sentence of fifteen years. In the future, the suggestion in this article is that the concept of free legal advisory assistance provided by the state must be provided to all suspects.